Electron–phonon processes of the silicon-vacancy centre in diamond - Kay D Jahnke; Alp Sipahigil; Jan M Binder; Marcus W Doherty; Mathias Metsch; Lachlan J Rogers; Neil B Manson; Mikhail D Lukin; Fedor Jelezko (New Journal of Physics, 2015)
We investigate phonon induced electronic dynamics in the ground and excited states of the negatively charged silicon-vacancy ( ${\rm Si}{{{\rm V}}^{-}}$ ) centre in diamond. Optical transition line widths, transition wavelength and excited state lifetimes are measured for the temperature range 4 K–350 K. The ground state orbital relaxation rates are measured using time-resolved fluorescence techniques. A microscopic model of the thermal broadening in the excited and ground states of the ${\rm Si}{{{\rm V}}^{-}}$ centre is developed. A vibronic process involving single-phonon transitions is found to determine orbital relaxation rates for both the ground and the excited states at cryogenic temperatures. We discuss the implications of our findings for coherence of qubits in the ground states and propose methods to extend coherence times of ${\rm Si}{{{\rm V}}^{-}}$ qubits.